Mental contamination among people in China: A replication of a moral manipulation experiment. (September 2022) - Tang, Tan; Fu, Zhongfang; Wang, Jianping
Abstract: Background and objectives: Mental contamination can be evoked by thoughts, images, and memories without having physically contacted any contaminants. Although several experiments have investigated the mechanism of mental contamination, none has been conducted in the Chinese socio-cultural context. Considering the potential cultural-sensitivity of mental contamination we replicated Elliott and Radomsky's experiment (2009) to examine whether an imagined immoral act would prompt mental contamination among female university students in China. Methods: We assigned participants ( n = 148) to 4 conditions in which they listened to an audio recording asking them to imagine that they had (a) shared a consensual kiss with a moral man, (b) shared a consensual kiss with an immoral man, (c) received a non-consensual kiss from a moral man, (d) or received a non-consensual kiss from an immoral man. Afterwards, they completed questionnaires, and their personal hygiene behaviours were recorded. Results: As in the precedent study, participants who imagined a non-consensual kiss reported greater feelings of mental contamination than ones who imagined a consensual kiss. Unlike in that study, however, imagining a consensual kiss from a moral man also aroused strong mental contamination. Limitations: It remains unclear which aspect of immoral acts (information or behaviour) weigh more in evoking mental contamination. Conclusions: The results suggest that imagining sexually immoral acts can evoke feelings of mental contamination among people in China. Nevertheless, cultural beliefs and attitude towards sexuality may play a role of causing the discrepancies. Highlights: Our study investigated on mental contamination in Chinese females. Imagining immoral events can evoke mental contamination among females in China. Imagining a consensual kiss with a moral man can evoke mental contamination. It could be attributed to morality and sexuality attitudes of Chinese females.